Cultural Narratives in the Development of Traditional Markets as Authentic Tourism Attractions in Yogyakarta - Syafii, Hisyam; Saadiah, Nur Khofifah; Alaldaya, Rudyn (CV. Austronesia Akademika, 2025)
Traditional markets in Yogyakarta are more than economic hubs; they serve as dynamic cultural spaces that reflect Javanese heritage and identity. With the rise of global tourism and shifting traveler interests toward authentic, immersive experiences, these markets have undergone significant transformation. This study investigates how cultural narratives are reconstructed and utilized in the development of Yogyakarta's traditional markets specifically Beringharjo, Ngasem, and Kranggan as authentic tourism attractions. Employing a qualitative critical ethnography within an interpretive paradigm, data were collected through participant observation, document analysis, and visual studies. Thematic coding and narrative analysis were used to interpret the findings. The research reveals that cultural elements such as rituals, symbols, and spatial arrangements are selectively commodified to meet tourist expectations while local communities actively negotiate and preserve their cultural integrity. Market stakeholders engage in “stagecraft” by adapting traditional practices for tourist consumption without fully losing their original meaning. The results also show the emergence of hybrid cultural expressions shaped by the interplay of digital technologies, tourism trends, and community agency. These narratives are neither static nor purely commercial; instead, they are continuously reinterpreted within broader socio-economic and political contexts. This study contributes to theoretical discussions in heritage tourism by emphasizing cultural narrative as a social construct, while offering practical recommendations for sustainable, participatory tourism models. Ultimately, it concludes that authenticity in tourism is a dynamic process shaped through ongoing dialogue between tradition and modernity.